2010
DOI: 10.1021/jo102109f
|View full text |Cite
|
Sign up to set email alerts
|

Direct, One-Pot Reductive Alkylation of Anilines with Functionalized Acetals Mediated by Triethylsilane and TFA. Straightforward Route for Unsymmetrically Substituted Ethylenediamine

Abstract: A new, robust, and reliable method has been developed for the selective reductive N-alkylation of primary and secondary aromatic amines with some functionalized acetals using TFA/Et(3)SiH as a reagent combination. A variety of unsymmetrically substituted ethylenediamines can be synthesized in a one-pot procedure in excellent yields at room temperature. This new procedure offers significant advantages over previous synthetic approaches, including brevity, mild reaction conditions, excellent yields, and high fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 26 publications
1
22
0
Order By: Relevance
“…[39] General procedure for reductive N-alkylation of anilines. TFA (1 mL) and TES (0.4 mL, 2.5 mmol) were added to a solution of the opportune aniline (1 mmol) and N-(2,2-dimethoxyethyl) acetamide [40] (206 mg, 1.4 mmol) in DCM (2 mL), and the resulting mixture was stirred at room temperature for 2 h under a nitrogen atmosphere. After cooling to 0°C, the reaction mixture was carefully neutralized with NaHCO 3 aqueous saturated solution of and diluted with DCM.…”
Section: -Methoxy-[11'-biphenyl]-2-amine (4 H)mentioning
confidence: 99%
“…[39] General procedure for reductive N-alkylation of anilines. TFA (1 mL) and TES (0.4 mL, 2.5 mmol) were added to a solution of the opportune aniline (1 mmol) and N-(2,2-dimethoxyethyl) acetamide [40] (206 mg, 1.4 mmol) in DCM (2 mL), and the resulting mixture was stirred at room temperature for 2 h under a nitrogen atmosphere. After cooling to 0°C, the reaction mixture was carefully neutralized with NaHCO 3 aqueous saturated solution of and diluted with DCM.…”
Section: -Methoxy-[11'-biphenyl]-2-amine (4 H)mentioning
confidence: 99%
“…To overcome this challenge, we turned our attention to a one-pot reductive N-alkylation procedure previously reported by Righi. 29 It was extended to the direct N-alkylation of a-f with acetals 7 and 8, in the presence of triethylsilane (TES), as nontoxic and stable reducing agent (Scheme 2). To obtain acetamide 7 from nitrile 5, we slightly modified a procedure involving the use of a large excess of NaBH 4 (7 eq.…”
Section: Chemistrymentioning
confidence: 99%
“…1 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 148. 29 Chloro-10H-phenothiazin-10-yl)-N-methylpropan-1-amine (2Ab).…”
Section: -(1011-dihydro-5h-dibenzo[bf]azepin-5-yl)-n-methylpropan-mentioning
confidence: 99%
“…[11][12][13][14] These polycyclic compounds are also identified as vital structural constituents useful intermediates in organic synthesis. [15][16][17] Moreover, they exhibit diverse medical functions as antidepressant, antiviral, antiepileptic, antiseizure, anticonvulsant, antimicrobial, antimalarial, anticancer, antioxidant antitumor, antibiotics and sirtuin-2 inhibitory activities. [18][19][20] Full literature survey for the applied methodologies in the synthesis of 5H-dibenz[b,f]azepine, dihydrodibenzazepine and tetrahydro-5H-dibenz[b,f]azocine systems revealed that synthesis of such heterocycles has been a prominent research objective for over a century and a variety of well established methods have been developed to access 5H-dibenzo[b,f]azepine derivatives.…”
Section: Introductionmentioning
confidence: 99%